The utilization of coal fly ash and red gypsum as fire insulation product - Ayu Wazira, Azhari; Azmil, Mohd Aris; Abdul Haqi, Ibrahim; Salwa, Mohd Zaini Makhtar; Mahyun, Ab Wahab (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.